Enhancing the Competence of Qurban Committees through Technical Training on Halal and Thoyyib Slaughtering in Pekanbaru, Riau - Endah Purnamasari; Elfi Rahmadani; Raudhatu Shofiah; Elfawati Elfawati (Smart Society, 2025)
Qurban is an annual Islamic ritual with profound spiritual and social significance; its proper implementation is essential to ensure that meat distributed to the public complies with halal and thoyyib principles. This study aimed to evaluate the effectiveness of an education- and practice-based training programme in improving participants’ knowledge and technical skills across key domains of qurban implementation (animal eligibility, slaughterer qualifications, facilities and hygiene, animal welfare, documentation, distribution ethics, and community engagement). The programme combined counselling, hands-on training, live slaughter demonstrations, and pre- and post-test evaluations with 70 participants predominantly younger adults (19–22 years old), mostly senior high school educated, and largely employed in the private sector. Overall knowledge improved from a mean pre-test score of 3.90 to 4.11 on the post-test (t = 3.35, p < 0.01), with the largest gains in animal welfare and slaughter-facility standards (e.g., infrastructure: Δ = 0.59; t = 4.32, p < 0.01). Several domains (e.g., hygiene, documentation, distribution, and ethical and community aspects) showed smaller, occasionally non-significant improvements, indicating areas for curricular strengthening through more structured modules, demonstration-rich sessions, and role-play simulations. The findings confirm that an education- and practice-led approach effectively enhances both knowledge and operational competence among qurban committee members. Sustainability is expected to be reinforced through collaboration with religious bodies, local authorities, and halal stakeholders to uplift community-level halal and thoyyib slaughter practices.